Protective Effect of Nerium oleander Distillate and Tarantula cubensis Alcoholic Extract on Cancer Biomarkers in Colon and Liver Tissues of Rats with Experimental Colon Cancer - Dik, Burak; Coskun, Devran; Er, Ayşe (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: Colon cancers are among the top three causes of cancer-related deaths. This study is a continuation of previous research aiming to identify effective treatments. Objective: This study investigated the effects of Tarantula cubensis alcoholic extract (TCAE) and Nerium oleander (NO) distillate on the levels of midkine, transforming growth factor (TGF)-β, vascular endothelial growth factor (VEGF), alpha-fetoprotein (AFP), cyclooxygenase (COX)-2, insulin-like growth factor (IGF) and caspase-3 in the liver and colon tissues of rats with experimentally induced colon cancer. Methods: The liver and colon tissues of rats were homogeneously divided into control, colon cancer (azoxymethane, AZM), AZM + TCAE, and AZM + NO distillate groups. The levels of midkine, TGF-β, VEGF, AFP, COX-2, IGF, and caspase-3 in the colon and liver tissues were measured by ELISA. Results: The levels of all parameters in colon and liver tissues in the AZM group were higher (p<0.05) than those in the control group. TCAE and NO distillate prevented (p < 0.05) increases in midkine, TGF-β, VEGF, AFP, COX-2, IGF, and caspase-3 levels in the colon. NO distillate prevented the increase in all parameters except IGF, whereas TCAE prevented the increase in all values apart from COX-2 and IGF levels in the liver (p<0.05). Conclusion: NO distillate and TCAE may prevent the studied markers from reaching specified levels observed in the colon in AZM-induced colon cancer. The increases in the levels of the parameters in the liver were not as severe as those in the colon; however, an 18-week study period may not be sufficient for liver metastasis formation. Future molecular studies should investigate the mechanisms and pathways of these treatments in greater detail.
Keywords: vascular endothelial growth factor